Strong Differential Subordinations Obtained with New Integral Operator Defined by Polylogarithm Function - K. AL-Shaqsi (International Journal of Mathematics and Mathematical Sciences)
By using the polylogarithm function, a new integral operator is introduced. Strong differential subordination and superordination properties are determined for some families of univalent functions in the open unit disk which are associated with new integral operator by investigating appropriate classes of admissible functions. New strong differential sandwich-type results are also obtained.